Natural and man-made V-gene repertoires for antibody discovery - Almagro, Juan C (Frontiers in Immunology, 2012)
Antibodies are the fastest-growing segment of the biologics market. The success of antibody-based drugs resides in their exquisite specificity, high potency, stability, solubility, safety and relatively inexpensive manufacturing process in comparison with other biologics. We outline here the structural studies and fundamental principles that define how antibodies interact with diverse targets. We also describe the antibody repertoires and affinity maturation mechanisms of human, mice and chickens, plus the use of novel single-domain antibodies in camelids and sharks. These species all utilize diverse evolutionary solutions to generate specific and high affinity antibodies and illustrate the plasticity of natural antibody repertoires. In addition, we discuss the multiple variations of man-made antibody repertoires designed and validated in the last two decades, which have served as tools to explore how the size, diversity and composition of a repertoire impact the antibody discovery process.